HUBUNGAN TINGKAT KECEMASAN PADA IBU BERSALIN DENGAN KEBERHASILAN INDUKSI PERSALINAN DI AURA SYIFA KABUPATEN KEDIRI - Savira Iluk Adkha; Mika - Mediawati; Arika Indah Setyarini (Poltekkes Kemenkes Malang, 2021)
Anxiety is the emotional reaction of the mother in labor which is associated with increased pain in labor. Induction of labor causes the mother to feel pain. The risk associated with failure of labor induction is cesarean delivery. The percentage of cesarean delivery in Indonesia increased from 7 percent in the 2007 IDHS to 17 percent in the 2017 IDHS. One of the factors affecting induction failure is the level of maternal anxiety facing labor pain, because the induction of labor is very long so the mother chooses cesarean section. The purpose of this study was to determine the relationship of anxiety levels in maternal with the success of labor induction in Aura Syifa Hospital, Kediri. Analytic survey research design with cross sectional survey design, sampling using Simple Random Sampling with a sample of 32 maternal women who were induced by misoprostol. The research instrument used the HRS A questionnaire and documentation sheet. Data were analyzed using chi square test with a significance level of 0.05 and obtained a value of p 0.005, which means there is a relationship between maternal anxiety levels with the success of labor induction in Aura Syifa Hospital, Kediri. The results showed that almost all of the respondents, namely 88.2 percent, experienced anxiety and experienced failure of labor induction as many as 15 respondents. The influence of anxiety levels in the success of labor induction, so that health workers are expected to play an active role in reducing maternal anxiety levels.